2020
DOI: 10.1111/petr.13799
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of antithrombotic prophylaxis in pediatric kidney transplantation—Results of an international survey on behalf of the European Society for Paediatric Nephrology

Abstract: Members of the "Transplantation Working Group" of the European Society for Paediatric Nephrology (ESPN)* * Collaborators including physicians who completed the survey are listed at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…Nevertheless, the majority of KTx professionals prefer to use some form of perioperative thromboprophylaxis, even though evidence-based recommendations are lacking. UFH appears to be the most favored thromboprophylactic agent for intraoperative use, possibly due to its beneficial pharmacokinetic characteristics, such as a low half-life and the fact that it is not eliminated by the kidney [ 11 , 12 ]. Dosing however varied considerably between 400 and 10,000 IU.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Nevertheless, the majority of KTx professionals prefer to use some form of perioperative thromboprophylaxis, even though evidence-based recommendations are lacking. UFH appears to be the most favored thromboprophylactic agent for intraoperative use, possibly due to its beneficial pharmacokinetic characteristics, such as a low half-life and the fact that it is not eliminated by the kidney [ 11 , 12 ]. Dosing however varied considerably between 400 and 10,000 IU.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…[9][10][11] In the absence of evidence-based recommendations and consensus guidelines, current antithrombotic strategies are often characterized by incongruent, non-standardized, and center-specific protocols for aP. 12,13 Therefore, this systematic review and meta-analysis were performed to collate, summarize, and quantify the available evidence on beneficial and adverse effects of aP in adult and pediatric KTx recipients.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of evidence‐based recommendations and consensus guidelines, current antithrombotic strategies are often characterized by incongruent, non‐standardized, and center‐specific protocols for aP 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Even though studies show conflicting results toward the beneficial effects for prevention of renal graft thrombosis, a recent publication of a survey done in 80 pediatric kidney transplant centers from 37 countries showed that antithrombotic prophylaxis was performed in 96% of the pediatric renal transplant centers 17 …”
Section: Introductionmentioning
confidence: 99%